KARAKTERISTIK FISIKA TEGANGAN ARUS DAN DIVERGENSI LASER DIODA BERBAGAI KEKUATAN DAYA YANG BERBEDA - Wijaya Widjanarka Natasaputra; Fatkhurrochman Fatkhurrochman; Riska Dwi Handayani (TRANSFORMASI, 2022)
The concept and theory of lasers was first put forward by Albert Einstein in 1917 and was first realized by researcher Theodore. H. Maiman in 1960. The invention of the laser is based on the theories of quantum physics, but research on the properties and optical characteristics of lasers, especially diode lasers is rarely carried out, so references for developing and applying them are very difficult to obtain. Lasers have coherent properties, which are parallel, massive, single-color (monochromatic) light propagations, which are different from incandescent white (polychromatic) light which is commonly known everyday from the sun, fire, lamps and so on. Laser diode devices have various types of power, which of course differ in the amount of voltage, current, strength of light in each condition (Uiga. E, 2014).The purpose of this research is to examine the physical characteristics of the diode laser, to determine the range of the current-voltage limits and the divergence angle in the radiant, to determine the characteristics of the laser diode with different powers.The research method used is experimental, which is carried out by testing variables and measuring the magnitude of the voltage, current, divergence of different powers from the diode laser.Based on the experimental results, the diode laser has a characteristic phase of the Volt-Ampere change called the laser phase. There are 3 phases that have been proven, namely the spontaneous emission phase, the transition phase, the stimulated emission phase and one characteristic that has been found, namely the power characteristics, the strong light (flux) (Uiga. E, 2014 ). The resulting data and variables can be used as a reference, study for research so that they can be used as a basis for further research.Keywords: Laser-Diode, Divergence, voltage, current, power